Produtividade de alho vernalizado proveniente de cultura de meristema - Ávila, Vinícius Tavares (2017)
The garlic culture has been under heavy external market pressure, with large volumes of garlic being imported at low prices, forcing Brazilian farmers to become technically looking for the reduction of production costs in order to compete with imported garlic. The objective of this study was to evaluate the effect of different periods of vernalization on the productivity of 5 different varieties of noble garlic free of viruses. Total bulb yield, shoot percentage and average bulb mass of the cultivars Chonan, Ito, Jonas, Quitéria and Caçador were evaluated. The cultivars Chonan and Caçador presented the highest commercial yield, confirming the good productivity of these clones in previous research. The treatments of 50 and 60 days of vernalization presented the highest values for commercial production and average mass of bulbs. The average number of bulbs was not affected by vernalization temperatures, maintaining the characteristics of the cultivars. The results confirmed that the period of 50 days of vernalization is an alternative for the production of clones that underwent the viral cleaning procedure.